Persaudaraan sebagai Pilar Toleransi dalam Pengembangan Budaya Pendamaian Dunia - Rahmah Rihhadatul ‘Aisy; Muharik Nadhloh Alhafidh; Risa Nisrina; Syifa Hasna Afifah; Supriadi Maud (STKIP Subang, 2026)
Cultural, religious, and social diversity is an inseparable reality of modern society. On the one hand, diversity serves as a source of social enrichment; on the other hand, it has the potential to generate conflict if not managed wisely. In this context, tolerance becomes a fundamental value in maintaining social harmony. However, sustainable tolerance requires a strong ethical foundation, one of which is fraternity. This study aims to examine the role of fraternity as a pillar of tolerance in the development of a culture of world peace. This research employs a qualitative approach using a library research method by analyzing academic books, national and international journal articles, and official documents from international organizations related to fraternity, tolerance, and peace. The findings indicate that fraternity plays a strategic role in strengthening tolerance through the cultivation of empathy, dialogue, and social responsibility. Furthermore, fraternity functions as both a preventive and conflict-resolution approach in managing social tensions and serves as a foundational element in fostering an inclusive and sustainable culture of world peace. Therefore, strengthening the value of fraternity is essential for promoting tolerance and achieving peaceful, just, and harmonious social life at local, national, and global levels.